Sweet syndrome induced by SARS-CoV-2 vaccines: A systematic review of patient-report studies - Yilai Jia; Boyang Fu; Liping Dong; Mingyi Zhao (Human Vaccines & Immunotherapeutics, 2023)
Since COVID-19 became a global pandemic in 2020, the development and application of SARS-CoV-2 vaccines has become an important task to prevent the spread of the epidemic. In addition to the safety and efficacy of COVID-19 vaccines, the adverse reactions caused by vaccines in a small number of people also deserve our attention. We aimed to discuss and analyze the possible causes of Sweet syndrome caused by the COVID-19 vaccine by integrating the effective information from 16 patients and combining it with the latest views on the innate immune mechanism. We searched the PubMed and Embase databases for published patient reports on the occurrence or recurrence of Sweet syndrome after COVID-19 vaccination. We summarized the basic information of the patients, the type of vaccination, the presence of underlying diseases, and the clinical manifestations, clinical treatment and prognosis of the patients. The results were reported in narrative methods and were sorted into tables. We initially identified 53 studies. 16 articles were included through full-text screening. Based on the table we compiled, we generally concluded that the first dose of any type of COVID-19 vaccine was more likely to cause Sweet syndrome than subsequent doses. Sweet syndrome may occur after COVID-19 vaccination. Clinicians should consider Sweet syndrome in addition to common adverse reactions such as anaphylaxis and infection when a patient presents with acute fever accompanied by nodular erythema, pustules, and edematous plaques after COVID-19 vaccination.